Superior supercapacitance behavior of oxygen self-doped carbon nanospheres: a conversion of Allium cepa peel to energy storage system - Ali, Gomaa A. M.; S., Supriya; Chong, Kwok Feng; Shaaban, Essam R.; H., Algarni; T., Maiyalagan; Hegde, Gurumurthy (Springer, 2021)
Mesoporous carbon nanospheres are produced from biowaste, Allium cepa peels, well known as “onion” dry peels using the catalyst-free pyrolysis method. The synthesis process involves an unusable bio-precursor that is accumulated in millions of tons per year. The obtained materials show nanosphere morphology with particles size of 63–66 nm and surface area up to 2962 m2 g−1. After pyrolysis at 800, 900, and 1000 °C, the carbon nanospheres are directly applied for supercapacitance study without further activation processes. The electrochemical studies show promising results such as high electrode capacitance of 189.4 at 0.1 A g−1 in 3 M KOH. Moreover, full cell symmetrical supercapacitor is fabricated and further investigated under a wide potential window up to 1.6 V. An excellent electrochemical behavior is observed for the supercapacitor in terms of high energy density of 22.1 Wh kg−1 at a power density of 39.6 W kg−1, high cyclic stability of 78%, and high coulombic efficiency of 90% over 4500 cycles at 0.5 A g−1. These studies support carbon nanospheres obtained from Allium cepa wastes to be used as promising materials for supercapacitor application.